Tafsir Pesan Pada Tradisi Budaya Punggahan Menyambut Ramadhan Dalam Perspektif Hermeneutika - Syafrudin Pohan; M. Fahru Rozy Stp (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
In Indonesia, one regional culture that still survives is the cultural practice of punggahan to welcome Ramadan. Although often difficult to understand by the general public, this tradition contains valuable messages and meanings. So, the purpose of this research is to hermeneutically analyze how the message is interpreted in relation to the cultural practice of puntungan in commemorating Ramadan. The case study method used in this research is a qualitative approach. In-depth interviews were used to gather information, and the implementation of the puntungan cultural tradition in a village in Tanah Seribu was observed. According to the research findings, punggahan, a cultural tradition used to welcome Ramadan, conveys messages of social cohesion, friendship, and appreciation for the blessings of Allah SWT. Understanding the messages and meanings contained in the punggahan cultural tradition can be aided by hermeneutics. However, this study also identified a number of concepts, including cultural context, personal background and perceptions, which may influence how the message is interpreted in the context of the upload. Therefore, it is important to consider such factors when interpreting messages from the punggahan cultural tradition in order to have a more thorough and accurate understanding.